2004
DOI: 10.1385/endo:25:1:01
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte Osmotic Fragility and Oxidative Stress in Experimental Hypothyroidism

Abstract: The present study was planned to explain the relation between erythrocyte osmotic fragility and oxidative stress and antioxidant statue in primary hypothyroid-induced experimental rats. Twenty-four Spraque Dawley type female rats were divided into two, as control (n = 12) and experimental (n = 12), groups weighing between 160 and 200 g. The experimental group animals have received tap water methimazole added standard fodder to block the iodine pumps for 30 d (75 mg/100 g). Control group animals were fed tap wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 20 publications
1
19
0
Order By: Relevance
“…Some workers suggest that hypothyroidism protects tissues against accelerated lipid peroxidation, although the data concerning oxidation / antioxidation in hypothyroidism are incomplete and contradictory (Isman et al, 2003;Venditti and Di Meo, 2006). In fact, Dariyerli et al, (2004) did not find any change in the content of malondialdehyde in rats with thiamizoleinduced hypothyroidism. However, following PQQ administration there was a significant increase in its level in all studied tissues.…”
Section: Discussionmentioning
confidence: 94%
“…Some workers suggest that hypothyroidism protects tissues against accelerated lipid peroxidation, although the data concerning oxidation / antioxidation in hypothyroidism are incomplete and contradictory (Isman et al, 2003;Venditti and Di Meo, 2006). In fact, Dariyerli et al, (2004) did not find any change in the content of malondialdehyde in rats with thiamizoleinduced hypothyroidism. However, following PQQ administration there was a significant increase in its level in all studied tissues.…”
Section: Discussionmentioning
confidence: 94%
“…This increased erythrocyte osmotic fragility may be attributed to the concomitant effects of heat and road transportation stresses, which have been shown to cause increased generation of free radicals in animals (Nazifi et al 2009) and increased free radical generation has been demonstrated to result in oxidative stress (i.e. an impairment of equilibrium between pro-oxidants and antioxidants) (Dariyerli et al 2004;Chakraborti et al 2008;Halliwell 2009). The reason that, erythrocytes are highly susceptible to oxidative stress as a result of high amount of unsaturated fatty acid content in their membranes (Altan et al 2003) further supports the fact that free radicals generation in stress, would decrease the antioxidants in the body (Tauler et al 2003;Nazifi et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Mano et al [15] found that the concentration of lipid peroxides, determined indirectly by the measurement of thiobarbituric acid reactants, did not change in hypothyroid rats when compared with the euthyroid animals. Dariyerli et al [227] showed that there is no statistically significant difference found between hypothyroid and control groups in the lipid peroxidation indicator MDA. The results of Yilmaz et al [228] who reported increased plasma, liver and muscle MDA levels in hypothyroid rats contradict our findings.…”
Section: Antioxidant Statusmentioning
confidence: 97%